Peran Wanita dalam Pengumpulan dan Penyebaran Hadis - Ginting, Ernawati; Akbar, Alwi Khomaid; Srg, M Agil; Hasim, Uday (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2024)
The role of women in collecting and disseminating hadith is very significant. Women not only narrated the hadith but also taught it and ensured its preservation for future generations. Even without their contributions, much important knowledge about Islamic teachings and the life of the Prophet Muhammad SAW might not have reached us. Therefore, this research will discuss further the role and contribution of women in the collection and dissemination of hadith which is studied using a qualitative research approach with the search library method. Meanwhile, descriptive qualitative research using the search library method is a research approach used to explore and describe existing phenomena using information sources from books, journals, digital databases, and other reading sources. The aim and benefit of this research is that it can provide insight and raise awareness of the important role of women in collecting and disseminating hadith. By understanding their contributions, we not only gain a more complete picture of Islamic history but also appreciate the efforts and dedication of women in preserving and spreading Islamic teachings.